Istotne cele małżeństwa katolickiego - Smoliński, Tomasz (Ius Matrimoniale, 2019)
Contemporary church legislation indicates two basic purposes of marriage: the good of the spouses and the birth of offspring. Today’s doctrine is based on the teaching of philosophers, theologians and doctors of the Church. In this work, considerations have been made regarding the important purposes of marriage, taking into account the views of scholars from ancient times, through the Middle Ages, to the Code of Canon Law of 1917, the Second Vatican Council and finally, the current Code of Canon Law of 1983.